(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article examines idioms involving body parts in both Uzbek and English, focusing on their cultural significance and impact on language learning. Body-part idioms enrich both languages by adding expressiveness and depth, bridging cultural understanding, and providing language learners with valuable insights into each culture. Learning such idioms enhances communication skills, fosters cultural appreciation, and makes language learning more engaging and effective.